Body Temperature Measuring Device Based On Nodemcu Esp8266 - Miza, Khairul; Ilham, Dirja Nur; Candra, Rudi Arif; Budiansyah, Arie; Harahap, Muhammad Khoiruddin (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2024)
Health is a state of well-being of the body, soul, and society that allows everyone to live productively socially, and economically. Health maintenance is an effort to overcome and prevent health disorders that require examination, treatment, and care. The research method of the body temperature measuring device uses a thermal camera based on the Internet of Things (IoT). It uses two parts, namely input and output, where the input is a thermal camera sensor that functions to measure body temperature in humans while the production is in the form of a display on the LCD and in the Blynk application. The purpose of this tool is to produce a tool that can read human body temperature. The tool that is produced will later be able to read body temperature accurately like existing measuring instruments. The results of the thermal camera tool will detect human body temperature at a distance of 2 to 3 cm. Where each body temperature reading will be displayed on the LCD and the Blynk application, making it easier to find out the body temperature that has been detected by the sensor.